Action and therapeutic targets of myosin light chain kinase, an important cardiovascular signaling mechanism - Qingzhi Ran; Aoshuang Li; Yuqing Tan; Yue Zhang; Yongkang Zhang; Hengwen Chen (Elsevier, 2024)
The global incidence of cardiac diseases is increasing, imposing a substantial socioeconomic burden on healthcare systems. The pathogenesis of cardiovascular disease is complex and not fully understood, and the physiological function of the heart is inextricably linked to well-regulated cardiac muscle movement. Myosin light chain kinase (MLCK) is essential for myocardial contraction and diastole, cardiac electrophysiological homeostasis, vasoconstriction of vascular nerves and blood pressure regulation. In this sense, MLCK appears to be an attractive therapeutic target for cardiac diseases. MLCK participates in myocardial cell movement and migration through diverse pathways, including regulation of calcium homeostasis, activation of myosin light chain phosphorylation, and stimulation of vascular smooth muscle cell contraction or relaxation. Recently, phosphorylation of myosin light chains has been shown to be closely associated with the activation of myocardial exercise signaling, and MLCK mediates systolic and diastolic functions of the heart through the interaction of myosin thick filaments and actin thin filaments. It works by upholding the integrity of the cytoskeleton, modifying the conformation of the myosin head, and modulating innervation. MLCK governs vasoconstriction and diastolic function and is associated with the activation of adrenergic and sympathetic nervous systems, extracellular transport, endothelial permeability, and the regulation of nitric oxide and angiotensin II. Additionally, MLCK plays a crucial role in the process of cardiac aging. Multiple natural products/phytochemicals and chemical compounds, such as quercetin, cyclosporin, and ML-7 hydrochloride, have been shown to regulate cardiomyocyte MLCK. The MLCK-modifying capacity of these compounds should be considered in designing novel therapeutic agents. This review summarizes the mechanism of action of MLCK in the cardiovascular system and the therapeutic potential of reported chemical compounds in cardiac diseases by modifying MLCK processes.